Abnormal sagittal patellar tilt during active knee flexion and extension on 4DCT might be associated with patellofemoral pain - Yurou Chen; Xin Liu; Bo Sheng; Mao Yuan; Furong Lv; Fajin Lv; Fan Yu; Jia Li (BMC Musculoskeletal Disorders)
Abstract Background The quadriceps during activities mainly affect patellar movement in the sagittal plane. This study was to analyze the pattern of sagittal patellar tilt in patellofemoral pain (PFP) patients by four-dimensional computed tomography (4DCT). Methods Thirty-four knees of PFP patients and 34 control knees were scanned with 4DCT. Patella-patellar tendon angle (P-PTA), patella-lateral tibial plateau angle (P-LTPA), patella-screen horizontal line angle (P-SHLA), articular facet of the patella-lateral tibial plateau angle (PA-LTPA), articular facet of the patella-screen horizontal line angle (PA-SHLA), and upper margin of the patella-quadriceps tendon angle (PU-QTA) were used to evaluate the sagittal patellar tilt. Two-factor repeated-measures ANOVA was used to compare all parameters between the two groups. Results At 30°−40° of flexion, P-PTA was significantly lower in PFP group than in control group (p = 0.004). At 0°–10°, PU-QTA was significantly higher in PFP group than in control group (p = 0.027). During flexion and extension, P-SHLA and PA-SHLA were significantly higher in PFP group than in control group, but there were no significant differences in P-LTPA and PA-LTPA. From − 10° to 30°, P-PTA decreased as the knee flexion angle increased. PU-QTA, P-LTPA, and PA-LTPA also decreased as the knee flexion angle increased, but P-SHLA and PA-SHLA increased. Conclusions In PFP group, sagittal patellar tilt was abnormal, and patella showed anterior tilt relative to the screen horizontal line during active knee flexion and extension. The pattern of patellar sagittal motion during dynamic process was consistent between PFP and control groups. The characteristics of patellofemoral sagittal alignment should not be ignored when analyzing patellofemoral stability.